O teorema de estabilidade de Lichnerowicz para aplicações holomorfas em variedades Kahler - Cunha, Antonio Wilson Rodrigues da (2011)
Our goal in this work is to present a theorem due to A. Lichnerowicz, which guarantees stability from applications holomorphic or antiholomorphic with compact domain between Kahler manifolds.